CHARACTERIZATION AND USE OF SUBSTRATES COMPOSED OF ORGANIC WASTE IN THE PRODUCTION OF Colubrina glandulosa PERKINS SEEDLINGS - Mendonça, Victória Maria Monteiro; Pereira, Marcos Gervasio; Silva, Vitória Duarte S; Fonseca Júnior, Ariovaldo Machado; Beutler, Sidinei Júlio; Silva, Tiago Paula (Floresta, 2021)
Urban organic waste has been gaining prominence in the composition of substrates, as it is a source of natural nutrients and a sustainable alternative to mitigate environmental impacts caused by improper waste disposal. The aim of this study was to characterize chemically and physically substrates based on organic waste and to evaluate the development of Colubrina glandulosa seedlings using composted urban tree pruning waste. Treatments consisted of different proportions of organic compost (CP), soil from the A horizon (SAH), aged manure (BM) and vermiculite, kept in tubes (Citropote®) with volume of 1.7 L. C/N ratio, water holding capacity (10 hPa), electrical conductivity, macroporosity, microporosity and total porosity of substrates before their use were determined. Substrate fertility analyses were carried out before and after seedling production. During the development of the seedlings, height (H) and stem diameter (SD) were measured at 60, 90 and 120 days. At 90 and 120 days, the seedlings were divided into shoots and roots to determine the dry mass of each compartment, Dickson quality index (DQI) and contents of nutrients (N, P, K, Ca and Mg). After the analysis of the results, it can be observed that the treatments with high proportions of CP had better physical characteristics, but also showed chemical limitation in the development of the seedlings. Treatments based on BM, SAH and lower proportion of CP had the highest average results for H, SD, H/SD ratio and DQI.